Community Service as a Catalyst for Digital Transformation in Early Childhood Education - Nurbatra, Laela Hikmah; Masyhud; Hartono (STAIN SULTAN ABDURRAHMAN KEPRI, 2025)
This community service project aims to improve the digital literacy abilities of early childhood education (ECE) teachers at TK Aisyiyah Bustanul Athfal 5, with a focus on utilizing Canva to create engaging learning materials. The program was carried out in three phases: planning, execution, and assessment. The preparatory phase included a requirements assessment via focus group discussions (FGDs), which indicated that although teachers were acquainted with Canva, they need more training to proficiently employ its functionalities for educational content development. Based on the findings, a systematic training curriculum was created, and facilitators, including lecturers and university students, were chosen for facilitating the sessions. The implementation phase comprised a two-week training program that combined theoretical discourse with practical application. Teachers were acquainted with digital literacy principles and instructed in the development of interactive instructional materials with Canva. The training included solitary tasks, group activities, and peer evaluations to improve learning results. During the evaluation phase, the training's impact was analyzed via focus group discussions to identify the teachers' confidence and preparedness to include digital technologies into their instruction. The findings indicate that the curriculum considerably enhanced instructors' capacity to use Canva for instruction, emphasizing the significance of ongoing digital literacy training for educators. Through the use of technology, this program shows how focused professional development may equip educators with useful skills to improve early childhood teaching.